Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/jocd.12357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of autologous activated platelet‐rich plasma injection on female pattern hair loss: A randomized placebo‐controlled study

Abstract: Platelet-rich plasma injections can be regarded as an alternative for the treatment of female pattern hair loss with minimal morbidity and a low cost-to-benefit ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 17 publications
4
74
0
Order By: Relevance
“…While early journal publications on PRP largely focused on case series reports, some comparative control studies have been conducted in humans, albeit using a variety of treatment regimens . Arguably, the most relevant trial design for local scalp injections of PRP is an intra‐control, defined area, quantitative analysis study.…”
Section: Introductionmentioning
confidence: 99%
“…While early journal publications on PRP largely focused on case series reports, some comparative control studies have been conducted in humans, albeit using a variety of treatment regimens . Arguably, the most relevant trial design for local scalp injections of PRP is an intra‐control, defined area, quantitative analysis study.…”
Section: Introductionmentioning
confidence: 99%
“…The forest plot in Figure shows that the study data favored PRP on increasing hair density in males and females when compared to placebo with a pooled mean difference of 30.35 (95% confidence interval 1.77‐58.93) and a P value of less than 0.00001. Five of those seven studies reported statistically significant results in favor of PRP . Difference of data between the groups of the rest of two studies was not statistically significant and did not favor any treatment group .…”
Section: Resultsmentioning
confidence: 90%
“…Three studies applied co‐interventions (minoxidil, finasteride, or polydeoxyribonucleotide) in addition to PRP in the experimental group and applied the same intervention in the control group without PRP . The rest of 10 studies compared platelet‐rich plasma to placebo (normal saline or distilled water) . If studies included males, then the studies used the Hamilton‐Norwood classification to categorize progression of male pattern hair loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations